Summer's quest - Elliott, Suzanne (Cincinnati, Ohio : Standard Pub., 1987)
A story left behind by thirteen-year-old Lindsey's mother after her death involves Lindsey in a mystery which draws her closer to her father, from whom she has drawn away in her grief.
Keywords: Fathers and daughters -- Fiction; Death -- Fiction; Mystery fiction